Productive and reproductive parameters of guinea pig (Cavia porcellus) of the Saños and Mantaro lines - Cruz, Danny Julio (2021)
The aim of this study was to determine the productive and reproductive parameters of the Saños and Mantaro guinea pig lines, developed at the Santa Ana Agrarian Experimental Station, in the central highlands of Peru. Records from the years 2017 to 2020 of 1773 and 1888 guinea pigs of the Saños and Mantaro lines, respectively, were analysed. The productive parameters evaluated were the weights at birth (PN), at weaning (PD) and at the fourth (P4), eighth (P8) and thirteenth week (P13). The reproductive parameters were litter size (TC) and calving interval (IP). The fixed effects considered in the model were genetic line (L), sex (S), calving number (NP), TC and season (Tp - trimesters). Covariates were included such as the mother’s weight at delivery (PMP); PN, PD, P4 and P8 in the productive parameters. The animal effect was included as random in the reproductive parameter models. The GLM and GLMM procedures of the R software (v. 4.0.2) were used to determine the productive and reproductive parameters, respectively. The body weight (production parameters) for the Saños and Mantaro lines were 153.3 ± 1.0 and 150.1 ± 1.0 g for PN, 289.1 ± 2.0 and 291.8 ± 2.1 g for PD, 407.6 ± 2.4 and 401.3 ± 2.9 g for P4, 629.9 ± 4.4 and 619.1 ± 4.5 g for P8, and 824.2 ± 4.7 and 817.2 ± 4.9 g for P13, respectively The reproductive parameters of the Saños and Mantaro lines were 88.0 ± 3.9 and 86.0 ± 3.8 days calving interval, respectively for IP, and 2.6 ± 0.05 and 2.6 ± 0.04 offspring, respectively for TC. Significant differences were found (p<0.05), but not biologically relevant for PN, P4, and P8 adjusted for the fixed effects and respective covariates, the Saños line being superior. There were statistical differences (p<0.05) for the TC, being higher in the Mantaro line; similarly non-significant differences in the PI (p> 0.05) in favour of the Saños line in PN, P4, P8 over the Mantaro line, while the latter exceeds the Saños line in TC.